2015
DOI: 10.1142/s0129183115500898
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular Automata occupant evacuation model considering gathering behavior

Abstract: A two-dimensional (2D) Cellular Automata (CA) random model is developed to simulate occupant evacuation considering gathering behavior. The movement process from random distribution to gathering state can be simulated based on the map of the position repulsive force. Evacuations with random distribution and gathering distribution are compared. Visual field means object area coverage considered by the individual in the current cell, representing by the radius of visual field, VR. The simulation results with VR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Static floor field and dynamic floor field are both used in this study. Static floor field focuses on the target exit and it is always fixed, and dynamic floor field concentrates on the densely populated area and it is dynamically updated when time advances [13], [37], [38].…”
Section: B Floor Fieldmentioning
confidence: 99%
“…Static floor field and dynamic floor field are both used in this study. Static floor field focuses on the target exit and it is always fixed, and dynamic floor field concentrates on the densely populated area and it is dynamically updated when time advances [13], [37], [38].…”
Section: B Floor Fieldmentioning
confidence: 99%
“…In the crowd simulation field, the social force model, cellular automata (CA) model and agent based model were common microscopic models, which were often used in crowd evacuation simulation. Zhao [25] used the cellular automaton model to simulate panic evacuation behaviors and discussed the effects of population density on aggregation. Their study found that the crowd gathered quickly when the indoor population density was low under the influence of the repulsive force.…”
Section: Related Workmentioning
confidence: 99%
“…6) Do the above until all the occupants finish their evacuation. For more details, please refer to our previous work [25] Table 1. For the accuracy of the data, all the results in this paper are the mean values of 10 times calculation in the same condition.…”
Section: Ca Modelmentioning
confidence: 99%
“…As shown in Figure 5, the occupants and the exit door are purposely separated by two rows of unfilled nodes to prevent the premature occurrence of jamming [25]. Figure 6 shows the results of EXODUS and the CA model.…”
Section: Case Fourmentioning
confidence: 99%